Environment Friendly Industrial Growth for Sustainability - Satapathy, Sanjay Kumar; Kanungo, Shree (International Research Journal of Management, IT & Social Sciences, 2016)
Any countryâs environmental problems are related to the level of its economic development, the availability of natural resources and the lifestyle of its population. In India, rapid growth of population, poverty, urbanization, industrialization and several related factors are responsible for the rapid degradation of the environment. Environmental problems have become serious in many parts of the country, and hence cannot be ignored.Â  80% of the total population of Odisha, a state of Eastern India depends on agriculture. But most of them are small and marginal farmers. 48% farmerâs households are indebted. The state in reality is the second poorest state in India today, next only to Bihar. Industrialization is the only alternative to develop the economic status of the state but the darker side of it is environmental pollution. Hence if growth of industry can be accelerated along with environmental protection then a balance can be maintained. So this paper examines the growth of cottage industries in the state of Odisha through different statistical analysis as this is an ecofriendly industry and simultaneously a prospective area for the growth of indigenous talent.